The Development of Professional Competency Test in Knowledge and Cognitive Skill for Computer Innovation and Digital Industry - Suwanroj, Thamasan; Saeung, Orawan; Leekitchwatana, Punnee; Kaewkamjan, Kanaporn (My University, 2023)
—This research aimed to 1) analyze the content of professional competencies, 2) create the professional competency test, and 3) check the quality of the professional competency test. The operation method was composed of three steps: 1) five experts (set 1) analyzed the qualitative data of the professional competencies, 2) five experts (set 2) built the professional competency test, and 3) experts (set 3) checked the quality of the professional competency test, and then two trials of the test were performed. The research showed that 1) the content analysis of professional competencies found ten indicators: six for knowledge and four for cognitive skills, including 100 issues of the required measurement list. A test with 100 items covered the course descriptions of seventeen subjects in five curriculum groups. 2) The creation result found the professional competency test, five multiple-choice questions. The respondents got one point when they answered correctly and no point when they answered incorrectly. The test comprised 100 items in two aspects: 57 items for knowledge and 43 for cognitive skills. 3) The result of the quality check revealed that the professional competency test was good. It had a good level of content validity (IOC = 0.80-1.00). Its difficulty was appropriate (p = 0.25-0.78). The discrimination was good (r = 0.44-0.96). There was validity with a good level of internal consistency (α = 0.87), and it had good construct validity (x2-Sig = 0.25, RMSEA = 0.03, RMR = 0.02 and AGFI = 0.97), (ρc = 0.97-0.98). This test can be used as a quality tool to measure the professional competency test in knowledge and cognitive skills for Computer Innovation and Digital Industry.
Keywords: knowledge and cognitive skills; professional competency test in knowledge and cognitive skills; qualification framework of learning outcomes; Test